Behavior of reduced beam section moment connection with reference to continuity plates: state-of-the-art review - Ajay, Kulkarni Swati; Gaurang.R, Vesmawala (Journal of Structural Engineering, 2024)
Welded flange bolted web, are the most commonly used connections for the seismic resistant design of a steel structures. During Post Northridge (1994) and Kobe (1995) earthquake for damaged beams and columns, observations indicated that, connections suffered damages due to brittle fracture. After this event, extensive research has been carried out worldwide to address the unexpected damage to welded steel moment resisting frames. Various methods were proposed for modifying the cyclic performance of the conventional connection for new construction and to retrofit of steel moment frames. Reduced beam section (RBS) is one of the several connection types pre-qualified for use in new steel moment frames in seismic zone. To form reduced section, some portion of the beam flanges at a short distance from column face is removed, so that the yielding and plastic hinge occurs within the trimmed area of flanges. This paper summarizes the recent studies and visualizes the scope for further study in research developments of RBS connection with reference to continuity plates.